Risk of lung disease in the PI*SS genotype of alpha-1 antitrypsin: an EARCO research project - Teresa Martín; Catarina Guimarães; Cristina Esquinas; Maria Torres-Duran; Alice M. Turner; Hanan Tanash; Carlota Rodríguez-García; Angelo Corsico; José Luis López-Campos; Eva Bartošovská; Jens-Ulrik Stæhr Jensen; José María Hernández-Pérez; et al. (Respiratory Research)
Abstract Background The PI*S variant is one of the most prevalent mutations within alpha-1 antitrypsin deficiency (AATD). The risk of developing AATD-related lung disease in individuals with the PI*SS genotype is poorly defined despite its substantial prevalence. Our study aimed to characterize this genotype and its risk for lung disease and compare it with the PI*ZZ and PI*SZ genotypes using data from the European Alpha-1 antitrypsin Deficiency Research Collaboration international registry. Method Demographic, clinical, functional, and quality of life (QoL) parameters were assessed to compare the PI*SS characteristics with the PI*SZ and PI*ZZ controls. A propensity score with 1:3 nearest-neighbour matching was performed for the most important confounding variables. Results The study included 1007 individuals, with PI*SS (n = 56; 5.6%), PI*ZZ (n = 578; 57.4%) and PI*SZ (n = 373; 37.0%). The PI*SS population consisted of 58.9% men, with a mean age of 59.2 years and a mean FEV1(% predicted) of 83.4%. Compared to PI*ZZ individuals they had less frequent lung disease (71.4% vs. 82.2%, p = 0.037), COPD (41.4% vs. 60%, p = 0.002), and emphysema (23.2% vs. 51.9%, p < 0.001) and better preserved lung function, fewer exacerbations, lower level of dyspnoea, and better QoL. In contrast, no significant differences were found in the prevalence of lung diseases between PI*SS and PI*SZ, or lung function parameters, exacerbations, dyspnoea, or QoL. Conclusions We found that, as expected, the risk of lung disease associated with the PI*SS genotype is significantly lower compared with PI*ZZ, but does not differ from that observed in PI*SZ individuals, despite having higher serum AAT levels. Trial registration www.clinicaltrials.gov (ID: NCT04180319).